First Results from a Study of DIBs with Thousands of High-Quality Massive-Star Spectra. Issue Volume 9:Issue S297(2013) (21st February 2014) - Apellániz, J. Maíz; Sota, A.; Barbá, R. H.; Morrell, N. I.; Pellerin, A.; Alfaro, E. J.; Simón-Díaz, S.
Abstract: We are using five different surveys to compile the largest sample of diffuse interstellar band (DIB) measurements ever collected. GOSSS is obtaining intermediate-resolution blue-violet spectroscopy of 2500 OB stars, of which 60% have already been observed and processed. The other four surveys have already collected multi-epoch high-resolution optical spectroscopy of 700 OB stars with different telescopes, including the 9 m Hobby-Eberly Telescope in McDonald Observatory. Some of our stars are highly-extinguished targets for which no good-quality optical spectra have ever been published. For all of the targets in our sample we have obtained accurate spectral types, measured non-DIB ISM lines, and compiled information from the literature to calculate the extinction. Here we present the first results of the project, the properties of twenty DIBs in the 4100-5500 Å range. We clearly detect a couple of previously elusive DIBs at 4170 Å and 4591 Å; the latter could have coronene and ovalene cations as carriers.